Roadside Geology of Massachusetts - James W. Skehan (Mountain Press, 2001)
Keywords: educational resources; GEOLOGY; massachusetts

Geologic Fieldtrip Guidebook database for North America (American Geolosciences Institute)
Keywords: educational resources; GEOLOGY; guidebooks; massachusetts

Bedrock Geologic Map of Massachusetts - Zen, E-an; Goldsmith, Richard; Ratcliffe, Nicholas M; Robinson, P; Stanley, Rolfe S; Hatch, Norman L; Shride, Andrew F; Weed, Elaine G A; Wones, David R (USGS Unnumbered Series, 1983)
(Zen et al., 1983) The 1:250,000 scale Bedrock Geologic Map of Massachusetts, published by the USGS in 1983, shows the distribution of the different rock units, faults, and other features that make up the bedrock of Massachusetts. It was compiled from published 1:24,000-scale maps., unpublished data, and field reconnaissance by the authors. Many areas of the state, however, have yet to be mapped thoroughly at 1:24,000 scale. A paper version can be ordered from the USGS Store (http://store.usgs.gov/) by searching for Product Number: 32370 or by clicking the links below. A two-volume text, The Bedrock Geology of Massachusetts, published in 1991, accompanies the map. The publication is catalogued as U.S. Geological Survey Professional Paper 1366 A-D (western Mass.) and 1366 E-J (eastern Mass.)   A variety of ways to download the map and text are listed in "Other Links" below.
Keywords: #MassGeology; #MassGeologyMap; #StateGeologicMap; bedrock geology; eastern MA; GEOLOGIC MAP; GEOLOGY; map; massachusetts; western MA

Preliminary bedrock geologic map of the Orange 7.5' quadrangle, Massachusetts (including portions of the Millers Falls and Athol 7.5' quadrangles) - Robinson, P.; Fernandez, M. (Open File Report, 2008)
The culmination of over 50 years of mapping and geologic investigation by U-Mass professor Peter Robinson and his students, this map details the structure and stratigraphy of the Oliverean gneiss domes and the continuation of the Bronson Hill sequence south into central Massachusetts.
Keywords: #BedrockMaps; #MGSPub; AMMONOOSUC; Athol; ATHOL FAULT; BEARS DEN FAULT; BEDROCK; BRONSON HILL; ERVING; GEOLOGIC MAP; GEOLOGY; LITTLETON; map; METAMORPHIC; MGS Publication; New Salem; Orange; PELHAM DOME; Petersham; Shutesbury; Warwick; Wendell

Preliminary compilation of the bedrock geology of the land area of the Boston 2 degree sheet, Massachusetts, Connecticut, Rhode Island and New Hampshire - Patrick J Barosh; Fahey, Richard J.; Pease, Maurice Henry, Jr. (USGS Open File Report, 1977)
Keywords: #MassGeology; #MassGeologyMap; bedrock geology; Connecticut; eastern MA; GEOLOGY; map; massachusetts; New Hampshire; Rhode Island

The American Geological Institute - News and Resources for geoscientists and teachers (AGI)
Keywords: #EducationalResources; #ProfessionalDevelopment; activities; classroom; curricula; earth science; education; GEOLOGY; K-12; lesson plans; news; schools; standards; teacher resources; teaching

Geology Tours of National Parks (NPS)
Provides information on the geology of national parks and related resources.
Keywords: #EducationalResources; #Fieldtrips; activities; classroom; curricula; earth science; education; GEOLOGY; groundwater; K-12; lesson plans; national parks; parks; schools; standards; teacher resources; teaching; water; water cycle

List of geology and science blogs on About.com (about.com)
Keywords: #Blogs; #EducationalResources; blogs; geologists; GEOLOGY; scientists; social media

National Park Service Teacher Resources (NPS)
Educational resources and links for teaching geology with examples from the National Parks
Keywords: #EducationalResources; #Fieldtrips; #SubjectResources; activities; classroom; curricula; earth science; education; GEOLOGY; groundwater; K-12; lesson plans; national parks; parks; schools; standards; teacher resources; teaching; water; water cycle

News and Current events in Earth Science on Geology.com (Geology.com)
Keywords: #Blogs; #EducationalResources; events; GEOLOGY; news

Tapestry of Time and Terrain (USGS)
Unites the geology and topography of the United States. Includes descriptions of major geologic and topographic features and an explanation of the geologic time periods
Keywords: #EducationalResources; #SubjectResources; classroom; curricula; earth science; education; GEOLOGIC MAP; geologic time; GEOLOGY; K-12; lesson plans; North America; schools; standards; teacher resources; teaching; U.S.

The U-Mass Geosciences publication series (U-Mass Amherst Dept. of Geosciences)
A series of publications on Massachusetts geology based on Master's and PhD theses by U-Mass students from the 1960s-1990s. These are a valuable resource and the only geologic data for many areas. ***Note: This list needs to be re-built in the biblio database and have its own page off of MGS website– it's no longer online.
Keywords: #BedrockMaps; #LegacyPublications; #MapsDataPublications; BEDROCK; GEOLOGY; maps; massachusetts; theses; U- Mass